2023
DOI: 10.1002/smtd.202201663
|View full text |Cite
|
Sign up to set email alerts
|

Improved Crystallization of Lead Halide Perovskite in Two‐Step Growth Method by Polymer‐Assisted “Slow‐Release Effect”

Abstract: Fast reaction between organic salt and lead iodide always leads to small perovskite crystallites and concentrated defects. Here, polyacrylic acid is blended with organic salt, so as to regulate the crystallization in a two‐step growth method. It is observed that addition of polyacrylic acid retards aggregation and crystallization behavior of the organic salt, and slows down the reaction rate between organic salt and PbI2, by which “slow‐release effect” is defined. Such effect improves crystallization of perovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
10
1
Order By: Relevance
“…As PAA concentration increases, crystallite size of PVSK also increases at first and then decreases. [ 36 ] Above analysis indicates that the “confinement effect” appears at relatively higher doping concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…As PAA concentration increases, crystallite size of PVSK also increases at first and then decreases. [ 36 ] Above analysis indicates that the “confinement effect” appears at relatively higher doping concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Strategies to reduce defects have been proposed, such as additive (or solvent) engineering to reduce bulk defects via controlling crystallization, post-treatment to passivate interfacial defects, , and ion substitution to control ion migration. It was reported that low-defect density perovskite films with high crystal plane orientation were prepared by introducing the presynthesized, intrinsically highly oriented two-dimensional (2D) Dion–Jacobson perovskite of (BDA)­PbI 4 (BDA = 1,4-butanediamine) into the PbI 2 solution as a seed for three-dimensional (3D) perovskite epitaxial growth, which finally demonstrated a PCE of 23.95% . The 2D Ruddlesden–Popper perovskite of (NpMA) 2 PbI 4 (NpMAI = 1-naphthalenemethylammoniumiodide) was introduced into the PbI 2 solution to modulate crystal growth, which led to a PCE as high as 24.37% .…”
mentioning
confidence: 99%
“…Meanwhile, the target films exhibited lower RMS, which is attributed to the decrease in crystallization rate, leading to improved continuity of FAI and the formation of a flat perovskite film. [ 30 ] The flat perovskite film suggests an improved interface contact between the perovskite layer and hole transport layer. Furthermore, when perovskite films prepared from precursor solutions aged for 48 h were exposed to air (15–25% RH), the original film showed partial decomposition after 42 days of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, they achieved a champion PCE of 24.1%. [29] Furthermore, in the twostep sequential deposition method, the fast reaction between organic salts and PbI 2 forms a dense perovskite layer on the surface of PbI 2 , preventing further diffusion of formamidinium (FA + ) into the interior of PbI 2 and insertion into the [PbI 6 ] 4− framework, [30][31][32] resulting in the formation of low-crystallinity perovskite films. [33,34] Zhao et al manipulated PbI 2 by introducing amphiphilic ions to control the stacking direction, orientation, and distribution of the perovskite layers.…”
Section: Introductionmentioning
confidence: 99%